2017
DOI: 10.1155/2017/4658543
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Seyoeum on Obesity, Insulin Resistance, and Nonalcoholic Fatty Liver Disease of High‐Fat Diet‐Fed C57BL/6 Mice

Abstract: Background This study was performed to evaluate the effect of Seyoeum (SYE), a novel herbal meal replacement, on insulin resistance and nonalcoholic fatty liver disease (NAFLD) in obese mice fed with a high-fat diet (HFD). Methods SYE contained six kinds of herbal powder such as Coix lacryma-jobi, Oryza sativa, Sesamum indicum, Glycine max, Liriope platyphylla, and Dioscorea batatas. Male C57BL/6 mice were divided into four groups: normal chow (NC), HFD, SYE, and HFD plus SYE (HFD + SYE). The mice in groups ot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 42 publications
0
7
0
Order By: Relevance
“…Studies demonstrated obesity-induced nonalcoholic fatty liver disease (NAFLD) in HFD-fed mice [32]. Therefore, we evaluated the effect of spilanthol on liver lipid accumulation in obese mice fed an HFD.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies demonstrated obesity-induced nonalcoholic fatty liver disease (NAFLD) in HFD-fed mice [32]. Therefore, we evaluated the effect of spilanthol on liver lipid accumulation in obese mice fed an HFD.…”
Section: Resultsmentioning
confidence: 99%
“…Here, spilanthol significantly suppressed body weight gain, reduced the serum levels of leptin and TC, and increased HDL-C, but had no effect on TG levels. In addition, HFD-induced obesity correlated with hepatic TG accumulation [32]. Thus, spilanthol diminished HFD-induced hepatic lipid accumulation in obese mice.…”
Section: Discussionmentioning
confidence: 99%
“…6 ). In addition, it was found that MRP could effectively reduce the level of inflammation and OS in mice with NAFLD, opening up a new road for research into the treatment of NAFLD in humans ( Na et al, 2017 ). This study also had potential limitations.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, elevated levels of SREBP-1c were reported in obese, insulin-resistant, and hyperinsulinemic ob/ob mice suffering from fatty livers which may be due to the transcriptional dependency on the occurrence of insulin receptor substrate-1 (IRS-1) [ 44 ]. Moreover, lipogenesis could be stimulated by high insulin levels during the incidence of insulin resistance via the SREBP-1c protein activation [ 45 ] leading to the inhibition of insulin receptor substrate-2 that allows the action of insulin on glucose metabolism [ 46 ].…”
Section: Discussionmentioning
confidence: 99%